KELAYAKAN DISTRIBUSI DAN KETERSEDIAAN AIR BERSIH DI DESA MOJO KECAMATAN PADANG KABUPATEN LUMAJANG - Mochtar Nova Mulyadi; Elida Novita; N. Nurhayati (Faculty of Agricultural Technology, University of Jember, 2018)
The limitation to get clean water causes the community to utilize the existing water resources. One of the villages needs clean water during the dry season in Mojo Village Padang District, Regency Lumajang. The need for clean water was increasing as the population growth. The population of the Mojo Village was 3,901 people. The needs of clean water were supplied from Jirun wellspring. The Jirun wellspring was located 20 meters lower than a residential area. The government of Lumajang Regency installed a hydrant pump to solve the problem for distributing the clean water from Jirun wellspring to the residential area. The flow rate of Jirun wellspring reached 22.91 l/s. The index of clean water criticality was 3.44% namely “uncritical” that indicated Mojo Village was abundant water availability. Keywords: dongki pump, water balance